Impact of Substrate‐Based Ablation of Ventricular Tachycardia on Cardiac Mortality in Patients With Implantable Cardioverter‐Defibrillators. (8th October 2015) - KOMATSU, YUKI; MAURY, PHILIPPE; SACHER, FRÉDÉRIC; KHAIRY, PAUL; DALY, MATTHEW; LIM, HAN S.; ZELLERHOFF, STEPHAN; JESEL, LAURENCE; ROLLIN, ANNE; DUPARC, ALEXANDRE; MONDOLY, PIERRE; AURILLAC‐LAVIGNOLLE, VALERIE; et al.
Mortality After VT Substrate Ablation: Introduction: This study sought to determine if the acute procedural outcome of ventricular tachycardia (VT) substrate ablation is associated with a mortality benefit in patients with implantable cardioverter‐defibrillators (ICD). Methods and Results: A total of 195 ICD recipients (65 ± 11years) with ischemic or nonischemic dilated cardiomyopathy underwent substrate‐based ablation targeting elimination of local abnormal ventricular activities (LAVA). Acute procedural success, which was defined as elimination of all identified LAVA in addition to the lack of VT inducibility, was achieved in 95 (49%) patients. During a median follow‐up of 23 months, patients with acute procedure success had a significantly lower incidence of ICD shocks compared to those with ablation failure (8% vs. 30%, P < 0.001). In multivariate analysis, acute procedural success was associated with a lower risk of VT recurrence (hazard ratio [HR] 0.30, 95% confidence interval [CI] 0.18–0.49, P < 0.001) and all‐cause mortality (HR 0.32, 95% CI 0.17–0.60, P < 0.001). While the impact of ablation success on mortality was not statistically significant in patients with LVEF > 35% (HR 0.45, 95% CI 0.15–1.34, P = 0.15) and those with NYHA class I/II (HR 0.63, 95% CI 0.29–1.40, P = 0.26), it was marked in patients with LVEF ≤ 35% (HR 0.30, 95% CI 0.14–0.62, P = 0.001) and NYHA class III/IV (HR 0.17, 95% CI 0.05–0.57, P = 0.004). Conclusions: LAVA elimination in addition to VT noninducibility as a procedural outcome for substrate‐based ablation is associated with reduced mortality and better VT‐free survival during follow‐up. This prognostic benefit may be most pronounced in patients with severe heart failure as indicated by severely depressed LV function and NYHA class III/IV symptoms.